FREQUENCY OF TRANSAMINITIS IN PATIENTS WITH DENGUE FEVER AND ASSOCIATION WITH DISEASE SEVERITY (Journal of Medical & Health Sciences Review, 2025)
Introduction: While dengue fever is prevalent in our country, local studies focusing on the association between liver enzyme abnormalities are scarce as evident from thorough literature searches. Hence the study was planned. Results of the study would provide vital information about liver enzyme derangements with dengue fever which would help clinicians in better management and patient counselling.Objective: To determine the frequency of transaminitis and the association of transaminitis with disease severity in patients with dengue fever.Materials and methods: This descriptive cross sectional study was carried out at the Department of Medicine, Shifa International Hospital, Islamabad during the period 5th November 2024 till 28th February 2025. A total of 192 male and female patients in the age range 18 to 70 years diagnosed with dengue fever were enrolled and their blood samples were analyzed for transaminitis.Results: Mean age was 37.23±10.402 years. Majority of the participants were aging less than 40 years (n = 117, 60.9%). Male patients were 143 (74.5%). 91 patients had severe disease (47.4%) and 98 patients had transaminitis (51.0%). The p value for association between transaminitis and severe disease was 0.000 (